Taxonomic review of Aegla marginata Bond-Buckup & Buckup, 1994 (Decapoda, Anomura, Aeglidae) with description of a new species - Moraes, Juliana Cristina Bertacini; Tavares, Marcos; Bueno, Sérgio Luiz De Siqueira (Zootaxa, 2017)
The taxonomy of Aegla marginata Bond-Buckup & Buckup, 1994 from three disjunct hydrographic basins is revised using morphological data. Aegla marginata is redescribed from the type-locality (Morretes, Paraná State, Brazil) and a new species, Aegla quilombola n. sp., is described (from Intervales State Park, São Paulo State, Brazil). Both species are illustrated in detail. Morphological data support and confirm a previous assumption based on molecular data of a paraphyletic relationship between populations previously known as Aegla marginata.